Dynamic knee valgus alignment in healthy young adults and its association with single leg triple hop distance and athletic single leg stability - Jassia Ramzan; Muhammad Osama; Ghania Riffat; Mirza Mohammed Waqar Baig; Fatima Aiman (Journal of the Pakistan Medical Association, 2021)
Objective The purpose of the current study was to determine the dynamic knee valgus angulation (DKVA) among sedentary young adults and the relationship of DKVA with triple hop distance and athletic single leg stability. Methods A cross sectional study was conducted on a sample of 72 healthy sedentary young adults aged 18-26 years out of which 29 (38.33%) were males and 43 (61.76%) were females. DKVA, single leg triple hop distance and athletic single leg stability were the outcome measurements for the study. Shapiro-Wilk and Kolmogorov Smirnov tests were used to determine normality of data. Independent t-test and Mann Whitney-U test were used for gender based comparison, paired t-test and Wilcoxon signed-rank test for comparing values of right and left leg, Freidman test for comparing the values of DKVA in different tasks and Pearson and Spearman correlation was used to determine relationship between two variables. Confidence interval was kept at 95% and p<0.05 was considered significant. Results DKVA was found to be lower for dominant leg in all tasks, and higher for single leg tasks as compared to drop jump screening test for both legs. Greater values of DKVA were observed in females in all tasks. Single leg triple hop distance and athletic single leg stability scores were higher in males as compared to females. No significant correlation of DKVA was observed with single leg triple hop distance and athletic single leg stability. Continuous...